Consistent LDL‐C response with evolocumab among patient subgroups in PROFICIO: A pooled analysis of 3146 patients from phase 3 studies. Issue 10 (21st October 2018) - Stroes, Erik; Robinson, Jennifer G.; Raal, Frederick J.; Dufour, Robert; Sullivan, David; Kassahun, Helina; Ma, Yuhui; Wasserman, Scott M.; Koren, Michael J.
Abstract : Background: Evolocumab significantly lowers low‐density lipoprotein cholesterol (LDL‐C) when dosed 140 mg every 2 weeks (Q2W) or 420 mg monthly (QM) subcutaneously. Hypothesis: LDL‐C changes are comparable among different patient subgroups in a pooled analysis of data from phase 3 trials. Methods: A total of 3146 patients received ≥1 dose of evolocumab or control in four 12‐week phase 3 studies. Percent change from baseline in LDL‐C for evolocumab 140 mg Q2W or 420 mg QM vs control was reported as the average of week 10 and 12 values. Quantitative and qualitative interactions between treatment group and subgroup by dose regimen were tested. Results: In the pooled analysis, treatment differences vs placebo or ezetimibe were similar for both 140 mg Q2W and 420 mg QM doses across ages (<65 years, ≥65 years); gender; race (Asian, black, white, other); ethnicity (Hispanic, non‐Hispanic); region (Europe, North America, Asia Pacific); glucose tolerance status (type 2 diabetes mellitus, metabolic syndrome, neither); National Cholesterol Education Program risk categories (high, moderately high, moderate, low); and European Society of Cardiology/European Atherosclerosis Society risk categories (very high, high, moderate, or low). Certain low‐magnitude variations in LDL‐C lowering among subgroups led to significant quantitative interaction P values that, when tested by qualitative interaction, were not significant. The incidences of adverse events were similar across groups treated with each evolocumab dosing regimen or control. Conclusions: Consistent reductions in LDL‐C were observed in the evolocumab group regardless of demographic and disease characteristics.